A gain enhanced multiband antenna using SRRs with defected ground structure - Samantaray D.; Bhattacharyya S.; Srinivas K.V. (My University, 2025)
The performance of tapered shaped octagonal patch antenna embedded with split ring resonators (SRRs) in its square slots along with defected ground has been analyzed in this paper for multiband frequency applications. The designed antenna operates over three distinct frequencies viz., 3.31 GHz, 6.50 GHz and 12.01GHz with the respective fractional bandwidths of 19.6%, 8.6% and 29.8%. The maximum return loss of -57 dB has been achieved over the band 10.36-13.95 GHz while the maximum realized gain of 22 dB has been obtained at 12.07 GHz. The antenna exhibits endfire radiation pattern in its far-field characteristics. The proposed antenna finds its applications in defense and military, satellite communication, several medical applications like cancerous cell detection, tumor and microimaging in medical analysis for determination of radio waves and also in many communication fields. © 2019 URSI. All rights reserved.